Academic libraries for commuter students : research-based strategies - Regalado, Mariana; Smale, Maura A. (ALA Editions, 2018)
"Did you know that more than 85% of U.S. undergraduates commute to college? Yet the literature geared to academic libraries overwhelmingly presumes a classic, residential campus. This book redresses that imbalance by providing a research-based look at the specific academic needs of commuter students. Edited by a team of librarians and anthropologists with City University of New York, the largest urban public university in the U.S, it draws on their ongoing research examining how these students actually interact with and use the library. The insights they've gained about how library resources and services are central to commuter students' academic work offer valuable lessons for other institutions. Presenting several additional case studies from a range of institution types and sizes, in both urban and suburban settings, this book provides rigorous analysis alongside descriptions of subsequent changes in services, resources, and facilities. Topics include why IUPUI interior designers decided to scrap plans to remove public workstations to make way for collaborative space -- how ongoing studies by University of North Carolina anthropologist Donna Lanclos shaped the design of the Family Friendly Library Room, where students may bring their children -- ways that free scanners and tablet lending at Brooklyn College supports subway studiers -- ideas from students on how best to help them through the use of textbook collections -- using ACRL's Assessment in Action model to learn about student engagement and outcomes with library instruction at a community college; and guidance on enlisting the help of anthropology students to conduct interviews and observations in an ethnographic study. With its emphasis on qualitative research, this book will help readers learn what commuter students really need from academic libraries"--Publisher's description